Ações coletivas no agronegócio: uma análise da produção científica no Brasil a partir de teses e dissertações (1998-2012). - Wenningkamp, Keila Raquel (2015)
Brazilian agribusiness has been characterized by the increasing presence of partnerships between individuals and organizations. This cooperation becomes necessary due to various changes in the current market scenario, which requires new forms of organization and coordination in order to make companies more competitive. It follows from this situation the adoption of governance structures based on collective, complementarity and mutual aid, called forms of collective actions. Thus, the aim of this research was to understand the Brazilian scientific production about collective actions in agribusiness, found in dissertations (master and doctorate levels) from 1998 to 2012. In other words, the aim is to investigate whether collective actions in agribusiness are been studied and if so, what are the features of scientific research conducted on the topic. So, this study was based on the Theory of Collective Action. In methodological terms, this research was characterized as a state-of-the-art study, a descriptive research, a bibliometric research and quantitative and qualitative approach. The main source of data collection was the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), covering dissertations (master and doctorate levels) in Management, Economics and Urban and Regional Planning from 1998 to 2012. Based on the results obtained from these dissertations, it was possible to point out the presence of researches in the area of collective actions in agribusiness and also that these have increased in recent years, but in number still relatively shy when considering the recurrence and the importance of these structures for agribusiness and the local and regional development. Concerning the main features found in these dissertations, it was observed that, in most cases, they are empirical studies, focused in collective models applied in the form of cooperatives, associations, networks and LPA (Local Productive Arrangements)/clusters. In addition, the agricultural sector was the most studied in the case studies and the South and Southeast regions concentrate both most of the studies and most of the collective forms studied empirically. Finally, based on the results of the relationship between the dissertation conclusions and the Theory of Collective Action, it was possible to observe that some benefits provided by collective actions developed in agribusiness are indeed relevant for both the actors involved, as to the surroundings. However, as the Theory of Collective Action advocates, the researchers also found the existence of obstacles related mainly to the presence of free riders, lack or failure of communication, negative reputation, lack of trust, lack of reciprocity and the absence of leadership.